UPAYA GURU DALAM PENANAMAN KEDISIPLINAN PADA ANAK USIA DINI DI TK AMANDA KECAMATAN TONRA KABUPATEN BONE - Sari, Fita; Basri, Hasan (Institut Agama Islam Negeri Bone, 2024)
This thesis discusses the Teacher`s Efforts in Instiling Discipline in Early Childhood at Kindergarten Amanda, Tonra District, Bone Regency. The main problems in thus study are how the teacher`s efforts in instilling discipline in group Bs students and what are the supporting factors and inhibiting factors of the teacher in istiling discipline in early childhood at Amanda Kindergarten, Bone Pute Village, Tonra District, Bone Regency. This is important to study to find out how the teacher`s efforts in instilling discipline in group B students and what are the supporting and inhibiting factors in instilling discipline in early childhood at Amanda Kindergarten , Bone Pute Village, Tonra District, Bone Regency. To obtain data from these problems, the authors use the field research method (field research) which uses descriptive qualitative research types with pedagogic and psychological approaches, to obtain the deired data using primary and secondary data. Then analyzed by: 1. Reducing data, 2. Presenting data, 3. Drawing conclusions. The result of this study indicate that 1) Teacher Efforts n Instiling Discipline in Early Childhood in Amanda Kindergarten, Tonra District, Bone Regency, 2) Supporting and inhibiting Factors of Teachers in Istiling Discipline in Early Childhood in Amanda Kindergarten, Tonra District, Bone Regency.